Accounting and Municipalities Performance: The Case of the Central Region of Portugal - Maria da Conceição da Costa Marques; José Ferreira Marques (Insights into Economics and Management Vol. 7, 2021)
This article examines the differences in the adoption and implementation of the reform of financial accounting in the Portuguese municipalities. The accrual accounting in the public sector has attracted great interest from researchers and academics. This approach was developed based on the idea that one way to modernize public sector management will be adopting similar accounting practices to the private sector. This study is based on a questionnaire sent to the financial officers of the Portuguese municipalities of Central Region of Statistics of Portugal, who had previously adopted the double entry accounting based on Official Accounting Plan of Local Authorities (POCAL). The questionnaire was structured in the same way for the whole target population. This study will be possible to verify, based on the responses obtained, if local authorities do what they are legally defined to do in the provision of financial information on the allocation of resources as well as on the development of performance indicators, based on accounting data.